Plan de Gestión para el Diseño de la Vicerrectoría de Investigación de la Universidad Técnica Nacional - Álvarez-Bolaños, Seidy María (Instituto Tecnológico de Costa Rica, 2013)
This project was carried out as a requirement for the Masters Degree Program on Project Management of the Costa Rica Technological Institute. Its main objective is to develop a Management Plan in order to outline the Research Vice Chancellor of the National Technical University. The specific objectives looked upon the fulfillment of a diagnosis on the main features of research areas from sixteen selected universities, not only from Costa Rica but from Latin America and the United States as well. Likewise, a model of Vice Chancellor was proposed, derived from such diagnosis, and management plans on human resources, costs, communications and scope were designed and integrated. An overall analysis of the web pages of the universities under consult was carried out. Direct interviews to the research field managers were applied when possible. Likewise, a review of the web pages of certain organizations linked to the research field was undertaken, considering government and non-government institutions. Among such organizations are CONARE, CONICIT and the World Conference on Higher Education. Actions were taken to ask advice of experts on research issues and financial topics related to them. As a result, a proposal for a Research Vice Chancellor was attained, from which a management plan was elaborated for its design. This constitutes the corner stone of the current document. The elaboration of the project followed the guidelines of the Project Management Institute (PMI).
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2012.
Keywords: Gestión de proyectos; Diseño; Vicerrectoría investigación; Investigación; Universidades